RELEVANSI PAKET JANUARI TAHUN 2006 DAN PERTUMBUHAN KESEHATAN PERBANKAN INDONESIA - Agung Waluyo (Jurnal Akuntansi Bisnis, 2017)
Bank Indonesia as the regulator of national banking in Indonesia is committed to accelerate the recuperation of national economic and banking. The introduction of January Package 2006 is focused on both the recapitalization of national banking. It has been proven that in 2009 the national economic and banking was not really affected by global crises which originated from the collapse of U.S. banking. Indonesia is one of the countries in Asia which was not impacted by global economical crises if compared to other Asian countries. Keyword : January Package 2009, Banking Recuperation